2020
DOI: 10.1002/mnfr.201900390
|View full text |Cite
|
Sign up to set email alerts
|

Gut Bacterial Metabolite Urolithin A Decreases Actin Polymerization and Migration in Cancer Cells

Abstract: Scope: Urolithin A (UA) is a gut-derived bacterial metabolite from ellagic acid found in pomegranates, berries, and nuts can downregulate cell proliferation and migration. Cell proliferation and cell motility require actin reorganization, which is under control of ras-related C3 botulinum toxin substrate 1 (Rac1) and p21 protein-activated kinase 1 (PAK1). The present study explores whether UA can modify actin cytoskeleton in cancer cells. Methods: The effect of UA on globular over filamentous actin ratio is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Tables 2 and 4 are most interesting, as CH redifferentiation or prevention of CH dedifferentiation would require prevention of actin polymerization or enhancement of actin depolymerization. Actin inhibitors (Table 2), such as chaetoglobosin A and J [362,363], cytochalasin B and D [364,365], latrunculin A and B [366,367], and urolithin A, which was only recently shown to decrease actin polymerization [368], have already been evaluated in clinical trials. Some ROCK inhibitors (Table 4) have also been tested in all clinical trial phases for the treatment of glaucoma and ocular hypertension [369] and could play a role in the treatment of acute lung injury [370].…”
Section: Discussionmentioning
confidence: 99%
“…Tables 2 and 4 are most interesting, as CH redifferentiation or prevention of CH dedifferentiation would require prevention of actin polymerization or enhancement of actin depolymerization. Actin inhibitors (Table 2), such as chaetoglobosin A and J [362,363], cytochalasin B and D [364,365], latrunculin A and B [366,367], and urolithin A, which was only recently shown to decrease actin polymerization [368], have already been evaluated in clinical trials. Some ROCK inhibitors (Table 4) have also been tested in all clinical trial phases for the treatment of glaucoma and ocular hypertension [369] and could play a role in the treatment of acute lung injury [370].…”
Section: Discussionmentioning
confidence: 99%
“…The most mature mechanism of Rac1 mediated cytoskeletal recombination is through PAKs (P21 activated kinase) (32). Both cell proliferation and cell movement require actin recombination, which is controlled by Rac1 and PAK1 (31). PAKs can be divided into two groups: one is PAK 1-3 and the other group is PAK 4-6 (33).…”
Section: Rac1 Regulates Cell Adhesion Morphology and Movementmentioning
confidence: 99%
“…The study showed Urolithin-A inhibited cell motility as well. 50) A lot of studies demonstrated that Urolithin-A induced cell cycle arrest and apoptosis in various type of cancer. Cell cycle regulation and apoptosis regulation are intimately connected each other.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, wound healing assay showed that Urolithin-A inhibited cell motility in Ishikawa cell. 50) Urolithin-A inhibited cell motility by regulating Akt pathway in human pancreatic cancer cell line, BxPC3, MiaPaCa2 and PANC1. 43)…”
Section: Urolithin-a Inhibits Cancer Metastasismentioning
confidence: 99%